Structural Analysis and Service Life Prediction of Rubberized Thin Surfacing Hot Mix Asphalt - Sebastianus Kristianto Nugroho; Ary Setyawan; Arif Budiarto (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Rubberized thin surfacing hot mix asphalt (RTSHMA) is a type of flexible pavement that is currently being developed. It can provide the same good performance as asphalt concrete–wearing course (AC-WC). Based on previous research, the use of crumb rubber in the asphalt mixture can provide several advantages, such as increasing the flexibility of the mix so that the pavement is more resistant to cracking. Based on research showing the advantages of rubberized asphalt, the idea emerged to apply it in the field, namely on the Palur–Sragen City Boundary section as wearing course. The method of analysis in this study was modeling the pavement structure with the KENPAVE and BISAR 3.0 programs. The analysis results showed that the AC-WC model and RTSHMA model have the same good performance because both of them have a service life of more than twenty years, which is the standard for flexible pavements. However, RTSHMA has an advantage, i.e., the thickness layer is 25% thinner than AC-WC’s. With a thinner layer than AC-WC but the same good performance, RTSHMA is worth considering as an alternative pavement, especially for overlays.